2021
DOI: 10.1007/s10549-021-06195-7
|View full text |Cite
|
Sign up to set email alerts
|

Congruence and trajectories of device-measured and self-reported physical activity during therapy for early breast cancer

Abstract: Purpose This study examines congruence between self-reported and device-measured physical activity data in women with early breast cancer and compares trajectories under different treatments. Methods Women with non-metastatic breast cancer were recruited before primary therapy. In four weeks distributed over six months after treatment start, patients reported time spent on work, transport, chores and sports via diary and wore Garmin® vivofit 3 acceleromete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The average adherence percentage was calculated for each segment. The intervention-based segments included studies with weeks 1 [ 48 , 49 ], 2 [ 27 , 55 ], 3 [ 50 , 52 , 57 ], 4 [ 36 , 37 , 53 ], 7 [ 28 ], 8 [ 32 , 33 , 34 ], 10 [ 24 , 30 , 41 ], 12 [ 20 , 21 , 23 , 25 , 26 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 54 , 56 ], 17 [ 29 ], 24 [ 22 , 31 ] and 43 [ 35 ]. In the graph, (1.84) indicates the studies grouped in this segment that had a one-week intervention with an average adherence of 84%.…”
Section: Resultsmentioning
confidence: 99%
“…The average adherence percentage was calculated for each segment. The intervention-based segments included studies with weeks 1 [ 48 , 49 ], 2 [ 27 , 55 ], 3 [ 50 , 52 , 57 ], 4 [ 36 , 37 , 53 ], 7 [ 28 ], 8 [ 32 , 33 , 34 ], 10 [ 24 , 30 , 41 ], 12 [ 20 , 21 , 23 , 25 , 26 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 54 , 56 ], 17 [ 29 ], 24 [ 22 , 31 ] and 43 [ 35 ]. In the graph, (1.84) indicates the studies grouped in this segment that had a one-week intervention with an average adherence of 84%.…”
Section: Resultsmentioning
confidence: 99%
“…However, a previous study showed that patient-reported physical activity is concordant with more objective accelerometers. 36 Finally, this study did not include a control group to compare the observed physical decline with patients without breast cancer. However, our research group is currently comparing the GARS questionnaire of older patients diagnosed with breast cancer with a similar cohort of older adults without breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to provide patients with sustainable motivational concepts after an intervention ( 27 ). Activity diaries alone might offer some motivation, but there are considerable discrepancies between this form of self-assessment and other methods to quantify physical activity ( 28 ).…”
Section: Introductionmentioning
confidence: 99%